Clinicians' Adherence to Guidelines on Evaluation of Hypertension in Children and Adolescents. (July 2016) - Hartz, Jacob; Li, Jennifer S.; Akintoye, Ololade O.; Hornik, Christoph P.
Background: Hypertension is increasingly prevalent among children. We sought to review provider adherence to the National High Blood Pressure Education Program (NHBPEP) recommendations at a single academic medical center. Methods: We identified children 3-18 years of age with hypertension based on outpatient visit International Classification of Diseases, Ninth Edition, Clinical Modification codes from 2006 to 2012. We calculated the odds of individual tests administration for ten recommended tests, adjusting for demographic characteristics. Results: We identified 3, 588 (1.7%) of 216, 855 children diagnosed with hypertension at a median age of 14 years (25th and 75th percentile 10 and 16, respectively). No child received all ten recommended tests. The median number of tests administered was 2 (1, 4) but varied significantly by race and age. Urine drug screen (<1%) and renin levels (1%) were the least common, whereas serum creatinine (49%) and echocardiogram (40%) were the most common tests. Male children were more likely to receive an echocardiogram (odds ratio 1.43; 95% confidence interval: 1.24-1.64), and black children and those ≥11 years old were less likely to have their serum creatinine checked. Adherence to the guidelines did not improve over time ( P = .24). Conclusion: Children evaluated for hypertension in the outpatient setting infrequently receive the diagnostic tests recommended in the NHBPEP's report. Test administration frequency varies by patient demographics but has not improved significantly over time.